Prevalence and predictive factors of psychological morbidity following facial injury: a prospective study of patients attending a maxillofacial outpatient clinic within a major UK city. Issue 4 (31st December 2018) - Wilson, Naomi; Heke, Sarah; Holmes, Simon; Dain, Victoria; Priebe, Stefan; Bridle, Christopher; Aylen, Imogen; Boyd, Caroline; Ramjaun, Gonca; Kanzaria, Amar
Abstract : Adults presenting to maxillofacial surgery services are at high risk of psychological morbidity. This study examined the prevalence of depression, post-traumatic stress disorder (PTSD), anxiety, drug and alcohol use, and appearance-related distress among maxillofacial trauma outpatients over medium-term follow-up. It also explored socio-demographic and injury-related variables associated with psychological distress to inform targeted psychological screening protocols for maxillofacial trauma services. Significant associations were found between level of distress at time of injury and number of traumatic life events with levels of depression at 3 months. No significant associations were found between predictor variables and PTSD at 3 months, or with any psychiatric diagnosis at 6 months. The lack of evidence for an identifiable subgroup of patients who were at higher risk of psychological distress indicated that routine screening of all maxillofacial trauma outpatients should be offered in order to best respond to their mental health needs. The feasibility of the medical team facilitating this is challenging and should ideally be undertaken by psychologists integrated within the MDT. This study led to the funding of a clinical psychologist to provide collaborative care with the maxillofacial surgeons, resulting in brief assessment and treatment to over 600 patients in the first year of the service.